Part III – March 1968 - Papers - Reproducible Diffusion of Zinc into GaAs: Application of Ternary Phase Diagram and the Diffusion and Solubility Analyses - H. C. Casey; M. B. Panish (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
The roles of the phase diagram and the diffusion and solubility analyses in the selection of sources for the diffusion of zinc into GaAs are discussed. Isothermal sections of- the phase diagram are described at 1000°, 775°, 744°, and 700°. Below 744° the three solid phases, Zn3As2, GaAs, and ZnAsz, may be in equilibrium. In the composition regions where the three solid phases are in equilibrium, the partial pressures of the components do not vary with composition and there is no liquid phase. A diffusion source composition within that region containing 5, 50, and 45 at. pct Ga, As, and Zn was selected to yield reproducible diffusion profiles without surface damage. The 5/50/45 ternary source Provides a significant improvement in the reproducibility and planarity of- the zinc diffusion as compared with other zinc diffusion sources that result from starting with elemental zinc, dilute solutions of zinc in gallium, or various combinations of zinc and arsenic. Several experimental diffision profiles for the 5/50/45 diffusion source have been determined. The profiles are very steep in the region of the junction and produce devices that exhibit step junction behavior. The junction depth varies as the square root of time. Diffusion at 700°C for 4 hr gives a 5-µ junction depth and a surface concentration of 2.4 x1020 cm-3. The surface concentration is enhanced by a factor of three and the junction depth decreased by a factor of ten as compared with diffusion with a starting source 01- elemental zinc. The differences in dijyusion behavior with these two sources are due primarily to the approximately 10' greater equilibrium As4 partial pressure for the 5/50/45 source. ThE most common technique for the preparation of GaAs p-n junctions for diverse applications ranging from switching diodes to injection lasers has been to diffuse zinc into the solid from the vapor phase. The zinc impurity has generally been provided by introducing into a diffusion ampoule elemental zinc, dilute solutions of zinc in gallium, or various combinations of zinc and arsenic. For the purpose of eliminating surface deterioration, zinc has been diffused into GaAs through SiO2 films1 and from zinc-doped SiO2 films.2 During a study of the injection and recombination mechanisms in GaAs junctions, we found that these diffusion techniques either resulted in nonreproducible diffusion profiles and nonplanar junction interfaces or were extremely inconvenient to use. An unpublished report by Allen and pearson3 emphasized that an understanding of diffusion requires relating the diffusion conditions and system compositions to the ternary phase diagram. Recent studies have made it possible to relate the effect of starting source composition on the GaAs sample surface and diffusion profile reproducibility and, in addition, to estimate the expected surface concentration and zinc diffusivity. These studies include the Ga-As-Zn phase diagram,415 the determination of the incorporation reaction for zinc as a substitutional impurity,6 and the analysis of the concentration dependence of the diffusion coefficient.' In this paper the role of the phase diagram in the selection of the starting diffusion source composition is illustrated, and an application of the diffusion and solubility analyses is used to demonstrate their utility in the estimation of surface concentration and diffusivity for various starting source compositions. Consideration of the isothermal sections of the ternary phase diagram shows that below about 744° C a composition region exists where the three solid phases Zn3As2, GaAs, and ZnAs2 are in equilibrium without a liquid phase. In this region the partial pressures of the components do not vary with composition, and thus the surface concentration and diffusivity depend only on temperature. A diffusion source composition within that region containing 5, 50, and 45 at. pct Ga, As, and Zn was selected. As will be described in detail, this diffusion source yields reproducible diffusion profiles without surface damage, planar junction interfaces, and steep profiles that result in devices with step junction behavior. Only closed diffusion systems are considered. Open or flowing vapor systems require the maintaining of constant vapor pressures in the flowing gas and represent control problems outside the scope of this discussion.